2008
DOI: 10.1080/10286020802320590
|View full text |Cite
|
Sign up to set email alerts
|

Portulene, a new diterpene fromPortulaca oleraceaL.

Abstract: Chromatographic fractionation of the chloroform extract of Portulaca oleracea L. growing in Egypt afforded a new clerodene diterpene portulene (1), in addition to the known compounds lupeol (2), beta-sitosterol (3), and daucosterol (4), which were reported for the first time from the title plant. The structures of the isolated compounds were unambiguously established through 1D, 2D, and mass spectral analyses. Co-treatment of CCl(4) hepatic injured rats with 70% alcohol extract of P. oleracea significantly res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 21 publications
1
59
0
1
Order By: Relevance
“…Recent research revealed a wide range of biological activities such as antifungal effect against dermatophytes of the genera Trichophyton, antinociceptive, antioxidant, and wound-healing activity. A bronchodilatory effect in asthmatic patients, skeletal muscle relaxant, and antifertility effect were also reported for P. oleracea (Elkhayat et al, 2008). Until now, however, there were no pharmacological studies upon the anxiolytic-like effects of P. oleracea.…”
Section: Introductionmentioning
confidence: 98%
“…Recent research revealed a wide range of biological activities such as antifungal effect against dermatophytes of the genera Trichophyton, antinociceptive, antioxidant, and wound-healing activity. A bronchodilatory effect in asthmatic patients, skeletal muscle relaxant, and antifertility effect were also reported for P. oleracea (Elkhayat et al, 2008). Until now, however, there were no pharmacological studies upon the anxiolytic-like effects of P. oleracea.…”
Section: Introductionmentioning
confidence: 98%
“…A bronchodilatory effect in asthmatic patients, skeletal muscle relaxant and antifertility effect were also reported for P.O. (Elkhayat et al, 2008). It has been described as a "power food" of future because of its high nutritive and antioxidant properties (Simopoulos et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…The hepatoprotective activities of hydroalcoholic extract of stems and leaves of P.O. in rats treated with CCl 4 (Elkhayat et al, 2008) or rifampicin (Kulkarni et al, 2007) were previously reported. The present study was designed to evaluate the protective effects of Portulaca oleracea against Paracetamol-induced hepatic toxicity in male rats.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, they were diminished in Po-treated group (−42%), most likely due to its antioxidant properties. Elkhayat et al [23] showed that treatment with alcoholic extract of Po restored the hepatic marker enzymes, which demonstrated hepatoprotective activity in hepatic injured rats.…”
Section: Plasma Albumin Uric Acid and Transaminases Activitiesmentioning
confidence: 99%